Mathematical coherence in science education: exploring curriculum alignment and student achievement in middle school - Incikabi, Semahat; Erbay, Oktay (Frontiers in Psychology, 2025)
ObjectiveThis study examines how the alignment between mathematics and science curricula affects secondary school students’ science achievement, focusing particularly on the dimension of mathematical consistency in textbook-based test items.MethodsUsing a mixed-methods research design, data were collected from 620 fifth and sixth-grade students in 11 public schools in Turkey. Based on their alignment with the grade-level mathematics curriculum, science questions were systematically categorized as mathematically connected (CCQ) or disconnected (CDQ).ResultsQuantitative analyses revealed that students demonstrated significantly lower achievement on CDQs, indicating that mathematical misalignments in science examinations negatively impacts students’ understanding and performance. Complementary clinical interviews indicated that students often possessed the necessary scientific knowledge but struggled with mathematical reasoning or representations that fell outside the scope of instruction.DiscussionThe findings highlight the importance of deliberate and systematic coordination between the two curricula, particularly in contexts where science and mathematics competencies are assessed concurrently. The study reveals that inconsistencies between curricula place students at a disadvantage in the assessment process and lead to conceptual fragmentation. Accordingly, recommendations have been made to curriculum developers, teachers, and policymakers to strengthen interdisciplinary consistency, increase fairness in assessments, and support students’ science achievement through consistent instructional design.